Preparation method of hydrotalcite modified fluorinated graphene corrosion-resistant self-repairing coating

By introducing hydrotalcite and corrosion inhibitor into the fluorinated graphene coating, the problems of high cost of fluorinated graphene and easy coating damage are solved, and efficient and lasting corrosion resistance and self-repair effects are achieved.

CN119775860AActive Publication Date: 2025-04-08SICHUAN UNIVERSITY OF SCIENCE AND ENGINEERING

Patent Information

Application Number
CN202411984091.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing fluorinated graphene coating is costly and can easily lead to local corrosion acceleration after damage, affecting corrosion resistance and service life.

Method used

Hydral talc is introduced into the surface of fluorinated graphene by co-precipitation method, reducing the amount of fluorinated graphene, and introducing corrosion inhibitors into the coating to improve the anion exchange capacity between layers and form a self-healing coating.

Benefits of technology

It significantly reduces the cost of the coating, while improving long-term corrosion resistance and self-repair performance, and extends the service life of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775860A_ABST
    Figure CN119775860A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a hydrotalcite modified fluorinated graphene corrosion-resistant self-repairing coating. The preparation method comprises the following specific steps: step 1, carrying out cleaning treatment on the surface of a to-be-treated matrix; step 2, adding fluorinated graphene into an ethylene glycol aqueous solution, and ultrasonically stirring and dispersing to obtain a solution A; the preparation method comprises the following steps: dissolving Zn (NO3) 2.6 H2O and Al (NO3) 3.9 H2O in water to prepare a solution B; dissolving a corrosion inhibitor in water to obtain a solution C; then, mixing the solution A, the solution B and the solution C, and reacting to obtain FG coated LDH powder; and step 3, mixing the FG coated LDH powder prepared in the step 2 with n-butyl alcohol and xylene, then adding epoxy resin, mixing, then carrying out ball milling, uniformly mixing a ball milling product with a polyamide curing agent, coating the surface of a to-be-treated matrix with the mixture, and curing to obtain the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heavy-duty anti-corrosion coatings in marine environments, and in particular to a method for preparing a hydrotalcite-modified fluorinated graphene corrosion-resistant self-repairing coating. Background Art

[0002] The application of organic coatings in marine equipment is an important means to protect metal structures from corrosion and environmental erosion. In the marine environment, due to factors such as high salinity, humidity and biological attachment of seawater, metal materials are prone to corrosion, which affects their performance and life. Therefore, the development of efficient and durable anti-corrosion coatings is crucial to ensure the safety and reliability of marine equipment.

[0003] Fluorinated graphene, as an advanced nanomaterial, is a derivative of graphene that has been fluorinated. Through the fluorination process, some carbon atoms are converted from their original sp 2 The hybridization state changes to sp 3 Hybridization, which not only retains the original large-sheet two-dimensional planar structure of graphene, but also introduces new CF bonds that give the material a series of excellent properties. These characteristics make fluorinated graphene show a broader application prospect in the fields of corrosion resistance and wear resistance than ordinary graphene. However, despite the many advantages brought by fluorinated graphene, there are still problems in practical applications. Because the synthesis process of fluorinated graphene is relatively complicated and requires the use of specific chemical reagents for fluorination treatment, the cost of raw materials increases, limiting its large-scale application. In addition, even the highest quality coatings may be damaged due to bumps, scratches, etc. during actual service. Once the coating is damaged, moisture and oxygen may penetrate into the metal surface, causing local corrosion to accelerate, and ultimately affecting the corrosion resistance and service life of the entire structure. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a method for preparing a hydrotalcite-modified fluorinated graphene corrosion-resistant self-healing coating. The preparation method can significantly reduce the cost of fluorinated graphene and enable the obtained coating to have long-term high corrosion resistance and self-healing performance, which is beneficial for the coating to provide long-term protection for the metal substrate, so as to solve the problems in the prior art of high cost of fluorinated graphene and accelerated local corrosion after the coating is damaged.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] A method for preparing a hydrotalcite-modified fluorinated graphene corrosion-resistant self-repairing coating, the specific steps are as follows:

[0007] Step 1: Clean the surface of the substrate to be treated;

[0008] Step 2: Add fluorinated graphene to an aqueous solution of ethylene glycol, and disperse by ultrasonic stirring to obtain solution A, wherein the concentration of fluorinated graphene in solution A is 0.4 mg / mL to 2.0 mg / mL, and the volume ratio of ethylene glycol to water is (1 to 3): (1 to 3); dissolve Zn(NO3)2·6H2O and Al(NO3)3·9H2O in water to prepare solution B, wherein the concentration of Zn(NO3)2·6H2O in solution B is 0.24 to 0.28 mol l / L, the concentration of Al(NO3)3·9H2O is 0.1-0.12 mol / L; the corrosion inhibitor is dissolved in water to obtain solution C, and the concentration of the corrosion inhibitor in solution C is 10 mg / mL-50 mg / mL; then, solution A, solution B and solution C are mixed, and the pH value is adjusted to 7-10; under a nitrogen atmosphere, the reaction is carried out at a constant temperature reflux for 12-24 hours, and then room temperature precipitation is carried out, centrifugation washing and vacuum freeze drying are carried out to obtain FG@LDH powder;

[0009] Step 3: Add the FG@LDH powder prepared in step 2 to a mixture of n-butanol and xylene, then add epoxy resin, mix and perform ball milling, mix the ball milling product evenly with the polyamide curing agent, apply it on the surface of the substrate to be treated, and obtain the coating after curing; wherein the mass ratio of epoxy resin, xylene, n-butanol, FG@LDH and polyamide is (30-100): (4-20): (2-10): (0.05-0.3): (20-80).

[0010] Preferably, in step 1, the substrate to be processed is a metal substrate, and 80-mesh corundum is used with a sandblasting accuracy of Sa2.5 or above. After sandblasting, the metal substrate is washed with clean water and ethanol in sequence, dried with cold air, and immersed in an acetone solution.

[0011] Preferably, in step 2, calculated by mass percentage, the fluorine content in the fluorinated graphene is 20% to 60%, the average grain size of the fluorinated graphene is 0.5 to 5 μm, and the ultrasonic stirring time is 1 to 2 h.

[0012] Preferably, in step 2, the corrosion inhibitor is one or both of sodium molybdate and disodium sebacate.

[0013] Preferably, in step 2, the reaction temperature is 50-100° C. under a nitrogen atmosphere, precipitation is carried out at room temperature for 12-24 hours, and vacuum freeze-drying is carried out for 12-24 hours.

[0014] Preferably, in step 3, the ball milling time is 0.5 to 5 hours, and the coating thickness after curing is 30 to 200 μm.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] 1. The preparation method of the present invention uses a coprecipitation method to grow hydrotalcite using fluorinated graphene as a substrate, achieving a mass ratio of 1:6 to 1:7. This means that during the synthesis process, the amount of fluorinated graphene required is less than the final hydrotalcite-modified fluorinated graphene. Since the preparation of fluorinated graphene is usually complicated and costly, such a mass ratio helps to significantly reduce the cost of the final product, making this high-performance material more competitive in the market and more valuable for practical application.

[0017] 2. The present invention can improve the problem of poor interface compatibility between fluorinated graphene and epoxy resin by introducing hydrotalcite on the surface of fluorinated graphene, thereby reducing the interface defects between the two. In addition, no harmful substances are introduced in the preparation method, ensuring the environmental friendliness of the entire preparation process.

[0018] 3. The present invention also found that hydrotalcite has a unique interlayer anion exchange capacity, allowing corrosion inhibitors to be inserted into its interlayer space, making it more effective in exchanging corrosive media such as chloride ions, and preventing chloride ions and other corrosive media from penetrating the coating to reach the metal surface, thereby protecting the metal from internal corrosion; and the ions released by the exchange can form a dense passivation film on the metal surface, which can effectively block the contact of moisture and oxygen, reduce the occurrence of corrosion reactions, and further protect the metal. This not only increases the versatility of the material, but also provides an additional mechanism for corrosion prevention.

[0019] 4. In the coating prepared by the preparation method of the present invention, the combination of the large-sheet structure of fluorinated graphene and the unique properties of hydrotalcite can effectively improve the long-term corrosion resistance of the coating. The large-sheet structure of fluorinated graphene provides a physical barrier to slow down the penetration of corrosive media; while hydrotalcite provides chemical protection through its interlayer anion exchange properties. The synergistic effect of these two mechanisms ensures that the coating can maintain its protective function for a long time even in harsh environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 These are electron microscope scanning images of the surfaces of the modified fluorinated graphene prepared in Example 1 and the unmodified fluorinated graphene used in Comparative Example 1; wherein a is Example 1 and b is Comparative Example 1.

[0021] Figure 2 The low-frequency impedance film value curves of the fluorinated graphene coatings prepared in Example 1 and Comparative Example 1 are respectively shown.

[0022] Figure 3 These are the results of the neutral salt spray resistance test of the fluorinated graphene coatings prepared in Example 1 and Comparative Example 1, respectively. DETAILED DESCRIPTION

[0023] The present invention will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the present invention belong to the scope of protection of the present invention.

[0024] Unless otherwise indicated in specific cases in the present invention, the numerical ranges listed herein include the upper and lower limits, and all integers and fractions within the range, and are not limited to the specific values ​​listed when defining the range.

[0025] 1. Preparation method of hydrotalcite-modified fluorinated graphene corrosion-resistant self-healing coating

[0026] Step 1: Clean the surface of the substrate to be treated;

[0027] Step 2: Add fluorinated graphene to an aqueous solution of ethylene glycol, and disperse by ultrasonic stirring to obtain solution A, wherein the concentration of fluorinated graphene in solution A is 0.4 mg / mL to 2.0 mg / mL, and the volume ratio of ethylene glycol to water is (1 to 3): (1 to 3); Zn(NO3)2·6H2O and Al(NO3)3·9H2O are dissolved in water to prepare solution B, wherein the concentration of Zn(NO3)2·6H2O in solution B is 0.24 to 0.28 mol / L, and the volume ratio of Al(NO3)3·9H2O is (1 to 3): (1 to 3); )3·9H2O has a concentration of 0.1 to 0.12 mol / L; the corrosion inhibitor is dissolved in water to obtain solution C, wherein the concentration of the corrosion inhibitor in solution C is 10 mg / mL to 50 mg / mL; then, solution A, solution B and solution C are mixed in a volume ratio of (4 to 6):(1 to 3):(1 to 3), and the pH value is adjusted to 7 to 10; in a nitrogen atmosphere, the mixture is refluxed at a constant temperature for 12 to 24 hours, precipitated at room temperature, washed by centrifugation and freeze-dried in vacuum to obtain FG@LDH powder;

[0028] Step 3: Add the FG@LDH powder prepared in step 2 to a mixture of n-butanol and xylene, then add epoxy resin, mix and perform ball milling, mix the ball milling product with a polyamide curing agent evenly, apply it on the surface of the substrate to be treated, and obtain the coating after curing; wherein the mass ratio of epoxy resin, xylene, n-butanol, FG@LDH and polyamide is (30-100): (4-20): (2-10): (0.05-0.3): (20-80).

[0029] The present invention takes into account the technical problems existing in the prior art, the cost of fluorinated graphene limits its large-scale use, and even the highest quality coating may be damaged due to bumps, scratches and other reasons during actual service. Once the coating is damaged, moisture and oxygen may penetrate into the metal surface, resulting in accelerated local corrosion, which ultimately affects the corrosion resistance and service life of the entire structure. Therefore, the present invention contemplates that a less amount of fluorinated graphene is used as much as possible so that the prepared coating can have a more excellent corrosion resistance. To this end, the present invention finds that the fluorinated graphene is modified and hydrotalcite is introduced into the surface of the fluorinated graphene to solve the problem of poor interface compatibility between the fluorinated graphene and the epoxy resin. At the same time, the present invention further finds that the corrosion inhibitor is inserted into the interlayer structure of the hydrotalcite, and the intercalation of the corrosion inhibitor makes it more strongly exchanged for corrosive media such as chloride ions, and the ions released by the exchange can form a dense passivation film on the metal surface, which plays a role in further protecting the metal, thereby avoiding the occurrence of corrosion of the metal substrate caused by the corrosive medium penetrating into the coating through these interlayer structures. The present invention surprisingly found that the prepared hydrotalcite-modified fluorinated graphene FG@LDH can achieve excellent corrosion resistance with only a small amount, which greatly reduces the production cost; at the same time, the present invention also found that the coating formed by adding FG@LDH to epoxy resin has a certain self-repairing function. Since the corrosion inhibitor is inserted between the hydrotalcite layers, even if the coating surface is inevitably damaged, the corrosion inhibitor between the hydrotalcite layers is slowly released, so that the exchanged released ions can form a dense passivation film on the surface of the metal substrate. This passivation film can self-repair the damaged coating to a certain extent, so that the damaged coating is repaired to a certain extent, thereby extending the service life of the coating.

[0030] In some embodiments of the present application, in step 1, the substrate to be treated is a metal substrate, and 80-mesh corundum is used with a sandblasting accuracy of Sa2.5 or above. After sandblasting, the metal substrate is cleaned with clean water and ethanol in sequence, dried with cold air, and immersed in an acetone solution to prevent oxidation on the surface of the metal substrate.

[0031] In some embodiments of the present application, in step 2, in solution A, the fluorination degree of the fluorinated graphene must reach a certain level to make the coating have strong hydrophobicity and high stability; if the fluorination degree is not enough, the hydrophobicity and stability cannot meet the requirements; but if the fluorination degree is too high, it will increase the production cost. Therefore, calculated by mass percentage, the fluorine content in fluorinated graphene can be 20%, 30%, 40%, 50%, 60%, etc., as well as all ranges and sub-ranges between the above values; the concentration of fluorinated graphene in solution A is controlled between 0.4 mg / mL and 2.0 mg / mL. If the concentration is too low, it will not have a corrosion-resistant effect, but if the concentration is too high, it will not only increase the production cost but also cause agglomeration and other phenomena. Therefore, the concentration of fluorinated graphene in solution A can be 0.4 mg / mL, 0.8 mg / mL, 1.0 mg / mL, 1.5 mg / mL, 2.0 mg / mL, etc., as well as all ranges and sub-ranges between the above values; at the same time, the size of fluorinated graphene needs to be controlled. If the size is too small, the lamellar structure advantage of fluorinated graphene is difficult to highlight, and if the size is too large, it will affect the arrangement of fluorinated graphene inside the coating, and ultimately affect the corrosion resistance of the coating. Therefore, the average grain size of the fluorinated graphene can be 0.5 μm, 1.0 μm, 2.0 μm, 3.0 μm, 4.0 μm, 5.0 μm, etc., and all ranges and sub-ranges between the above values; the ultrasonic stirring time can be 1 h, 1.5 h, 2 h, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.

[0032] In some embodiments of the present application, in step 2, too high concentrations of solution A, solution B and solution C will cause the final powder structure to be unformed, and too low concentrations will make the final prepared coating have poor anti-corrosion effect. Therefore, the concentration of Zn(NO3)2·6H2O in solution B can be 0.24mol / L, 0.25mol / L, 0.26mol / L, 0.27mol / L, 0.28mol / L, etc., and all ranges and sub-ranges between the above values; the concentration of Al(NO3)3·9H2O can be 0.10mol / L, 0.11mol / L, 0.12mol / L, etc., and all ranges and sub-ranges between the above values; in solution C, the concentration of the corrosion inhibitor can be 10mg / mL, 20mg / mL, 30mg / mL, 40mg / mL, 50mg / mL, etc., and all ranges and sub-ranges between the above values; it should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.

[0033] In some embodiments of the present application, in step 2, the corrosion inhibitor is one or both of sodium molybdate and disodium sebate. The corrosion inhibitors selected here are all environmentally friendly corrosion inhibitors, which will not cause environmental pollution and have excellent corrosion inhibition effects. Sodium molybdate can effectively prevent metal corrosion in both aerobic and anaerobic environments, but other corrosion inhibitors do not have this effect; disodium sebate can also reduce the friction coefficient and form a lubricant film on the surface of the friction pair, so that the friction performance of the prepared coating is better, and other corrosion inhibitors do not have this effect.

[0034] In some embodiments of the present application, in step 2, the reaction temperature under nitrogen atmosphere can be 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, etc., and all ranges and sub-ranges between the above values; the room temperature precipitation time can be 12h, 16h, 20h, 24h, etc., and all ranges and sub-ranges between the above values; the vacuum freeze-drying time can be 12h, 16h, 20h, 24h, etc., and all ranges and sub-ranges between the above values; it should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.

[0035] In some embodiments of the present application, in step 3, the ball milling time can be 0.5h, 1h, 2h, 3h, 4h, 5h, etc., and all ranges and sub-ranges between the above values; it should be understood that, in the implementation scheme, any of the above ranges can be combined with any other ranges.

[0036] 2. Examples and Comparative Examples

[0037] Example 1

[0038] (1) Workpiece pretreatment: The carbon steel workpiece is sandblasted.

[0039] (2) Preparation of hydrotalcite-modified fluorinated graphene: 50 mL of deionized water without CO2 and 50 mL of ethylene glycol were weighed into a three-necked flask, 0.1 g of fluorinated graphene was added and dispersed by ultrasonic stirring for 1 h to obtain solution A. 2.082 g of Zn(NO3)2·6H2O and 1.125 g of Al(NO3)3·9H2O were weighed and dissolved in 25 mL of deionized water without CO2 to obtain solution B. 0.5 g of sodium molybdate was dissolved in 25 mL of deionized water without CO2 to obtain solution C. Solutions A, B, and C were mixed and the pH was adjusted to 8.5. Under N2 atmosphere, the reaction was refluxed at 80°C for 12 h and then precipitated for 12 h. Finally, the mixture was centrifuged and washed and vacuum freeze-dried for 24 h to obtain 0.6-0.7 g of FG@LDH(M).

[0040] (3) Preparation of coating: The prepared FG@LDH(M) was added to a diluent containing n-butanol and xylene, wherein xylene and n-butanol were mixed in a mass ratio of 2:1. Then, epoxy resin E-44 was added, and the mixture was fully stirred to form a mixture, and the mixture was stirred by ball milling with a sand grinder. Then, the obtained product was evenly mixed with polyamide 650 curing agent, stirred for 10 minutes, and vacuumed to obtain FG@LDH(M) modified epoxy resin. The mass ratio of epoxy resin, FG@LDH(M), diluent, and polyamide 650 curing agent was 10:0.3:8:8. Finally, the prepared FG@LDH(M) modified epoxy resin was coated on the Q235 carbon steel surface after sandblasting, and the film thickness was controlled to be 110±10μm.

[0041] Comparative Example 1

[0042] An improvement was made on the basis of Example 1, except that: an equal amount of unmodified fluorinated graphene was used to replace FG@LDH. The other steps were exactly the same as those in Example 1, and an unmodified fluorinated graphene coating was obtained.

[0043] Example 2

[0044] (1) Workpiece pretreatment: The carbon steel workpiece is sandblasted.

[0045] (2) Preparation of hydrotalcite-modified fluorinated graphene: 50 mL of deionized water without CO2 and 50 mL of ethylene glycol were weighed into a three-necked flask, 0.1 g of fluorinated graphene was added and dispersed by ultrasonic stirring for 1 h to obtain solution A. 2.082 g of Zn(NO3)2·6H2O and 1.125 g of Al(NO3)3·9H2O were weighed and dissolved in 25 mL of deionized water without CO2 to obtain solution B. 0.5 g of disodium sebacic acid was dissolved in 25 mL of deionized water without CO2 to obtain solution C. Solutions A, B, and C were mixed and the pH was adjusted to 9. Under N2 atmosphere, the reaction was refluxed at 50°C for 12 h and then precipitated for 12 h. Finally, the mixture was centrifuged, washed, and vacuum freeze-dried for 24 h to obtain 0.6-0.7 g of FG@LDH(SB).

[0046] (3) Preparation of coating: The prepared FG@LDH(SB) was added to a diluent containing n-butanol and xylene, wherein the xylene and n-butanol were mixed in a mass ratio of 2:1. Then, epoxy resin E-44 was added, and the mixture was fully stirred to form a mixture, and the mixture was stirred by ball milling with a sand grinder. Then, the obtained product was evenly mixed with polyamide 651 curing agent, stirred for 10 minutes, and vacuumed to obtain FG@LDH(SB) modified epoxy resin. The mass ratio of epoxy resin, FG@LDH(SB), diluent, and polyamide 651 curing agent was 10:0.3:8:4. Finally, the prepared FG@LDH(SB) modified epoxy resin was applied to the Q235 carbon steel surface after sandblasting, and the film thickness was controlled to be 110±10μm, and then cured at 25-30°C for 72h to obtain FG@LDH(SB) coating.

[0047] Example 3

[0048] (1) Workpiece pretreatment: The carbon steel workpiece is sandblasted.

[0049] (2) Preparation of hydrotalcite-modified fluorinated graphene: 50 mL of deionized water without CO2 and 50 mL of ethylene glycol were weighed into a three-necked flask, 0.1 g of fluorinated graphene was added and dispersed by ultrasonic stirring for 1 h to obtain solution A. 2.082 g of Zn(NO3)2·6H2O and 1.125 g of Al(NO3)3·9H2O were weighed and dissolved in 25 mL of deionized water without CO2 to obtain solution B. 0.25 g of disodium sebacate and 0.25 g of sodium molybdate were dissolved in 25 mL of deionized water without CO2 to obtain solution C. Solutions A, B, and C were mixed and the pH was adjusted to 8.5. Under N2 atmosphere, the reaction was refluxed at 50°C for 12 h and then precipitated for 12 h. Finally, 0.6-0.7 g of FG@LDH(MS) was obtained by centrifugation washing and vacuum freeze drying for 24 h.

[0050] (3) Preparation of coating: The prepared FG@LDH(MS) was added to a diluent containing n-butanol and xylene, wherein the xylene and n-butanol were mixed in a mass ratio of 2:1. Then, epoxy resin E-44 was added, and the mixture was fully stirred to form a mixture, and the mixture was stirred by ball milling with a sand grinder. Then, the obtained product was mixed evenly with polyamide 650 curing agent, stirred for 10 minutes, and vacuumed to obtain FG@LDH(MS) modified epoxy resin. The mass ratio of epoxy resin, FG@LDH(MS), diluent, and polyamide 650 curing agent was 10:0.3:8:6. Finally, the prepared FG@LDH(MS) modified epoxy resin was coated on the Q235 carbon steel surface after sandblasting, and the film thickness was controlled to be 110±10μm, and then cured at 25-30°C for 72h to obtain FG@LDH(MS) coating.

[0051] 3. Performance Analysis

[0052] 1. Microscopic morphology test

[0053] Taking Example 1 and Comparative Example 1 as examples, the microscopic morphologies of FG@LDH(M) prepared in Example 1 and unmodified fluorinated graphene were observed. Figure 1 As shown, Example 1 ( Figure 1 The hydrotalcite of a) basically grows vertically on the surface of fluorinated graphene, and its size is about 50-200 nm; Comparative Example 1 ( Figure 1 The fluorinated graphene in b) has an obvious lamellar structure and a size of about 1000 nm. This indicates that hydrotalcite can be successfully introduced onto the surface of fluorinated graphene by the preparation method described in the present application.

[0054] 2. Electrochemical impedance spectroscopy experiment

[0055] The coatings obtained in Examples 1 to 3 and Comparative Example 1 were subjected to electrochemical impedance spectroscopy testing in a 3.5 wt % NaCl solution. The low frequency impedance modulus curves are shown in FIG. Figure 2 After 1200h of testing, the coating of Example 1 showed a trend of first decreasing, then increasing and finally stabilizing, which is closely related to the exchange of anions between the hydrotalcite layers. The release of the corrosion inhibitor effectively played a role in further protecting the carbon steel, and the long-term low-frequency impedance modulus was always maintained at 10 10 Ω·cm 2 , which is 2 to 3 orders of magnitude higher than that of the coating in Comparative Example 1. It can be seen that the modified epoxy coating FG@LDH(M) prepared with the same amount of FG and FG@LDH(M) has better corrosion resistance. 0.1gFG can produce 0.6g to 0.7g FG@LDH(M), which greatly reduces the application cost of FG in anti-corrosion coatings. The same is true for Examples 2 and 3. The low-frequency impedance modulus of the FG@LDH coatings prepared in Examples 2 and 3 is always maintained at 10 10 Ω·cm 2 .

[0056] 3. Neutral salt spray test

[0057] The carbon steel with modified coatings prepared in Examples 1 to 3 and Comparative Example 1 was placed in a neutral salt spray test chamber and tested with 5% sodium chloride at a test temperature of 35°C. The steel was taken out and photographed at regular intervals. The results of the neutral salt spray test are shown in Figure 1. Figure 3 As shown, Example 1 ( Figure 3 ) has a salt spray resistance of more than 800 h, and because the hydrotalcite has interlayer anion exchange properties, the scratches show obvious signs of shrinking, which indicates that the coating prepared in Example 1 is undergoing self-repair. Figure 3) has a salt spray resistance of less than 72 h. The salt spray resistance of Example 2 and Example 3 reaches more than 700 h and more than 900 h. The above results show that the fluorinated graphene modified by the hydrotalcite intercalated with sodium molybdate or disodium sebacic acid corrosion inhibitor significantly improves the salt spray resistance of the coating, which can better meet the application requirements of the marine environment; and Example 2 and Example 3 also show a certain self-repairing ability.

[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the technical solution. Those skilled in the art should understand that those modifications or equivalent substitutions of the technical solution of the present invention that do not depart from the purpose and scope of the technical solution should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a hydrotalcite-modified fluorinated graphene corrosion-resistant self-repairing coating, characterized in that: The specific steps are as follows: Step 1: Clean the surface of the substrate to be treated; Step 2: Add fluorinated graphene to an aqueous solution of ethylene glycol, and disperse by ultrasonic stirring to obtain solution A, wherein the concentration of fluorinated graphene in solution A is 0.4 mg / mL to 2.0 mg / mL, and the volume ratio of ethylene glycol to water is (1 to 3): (1 to 3); Zn(NO3)2·6H2O and Al(NO3)3·9H2O are dissolved in water to prepare solution B, wherein the concentration of Zn(NO3)2·6H2O in solution B is 0.24 to 0.28 mol / L, and the volume ratio of Al(NO3)3·9H2O is (1 to 3): (1 to 3); )3·9H2O has a concentration of 0.1 to 0.12 mol / L; the corrosion inhibitor is dissolved in water to obtain solution C, wherein the concentration of the corrosion inhibitor in solution C is 10 mg / mL to 50 mg / mL; then, solution A, solution B and solution C are mixed in a volume ratio of (4 to 6):(1 to 3):(1 to 3), and the pH value is adjusted to 7 to 10; in a nitrogen atmosphere, the mixture is refluxed at a constant temperature for 12 to 24 hours, precipitated at room temperature, washed by centrifugation and freeze-dried in vacuum to obtain FG@LDH powder; Step 3: Add the FG@LDH powder prepared in step 2 to a mixture of n-butanol and xylene, then add epoxy resin, mix and perform ball milling, mix the ball milling product evenly with the polyamide curing agent, apply it on the surface of the substrate to be treated, and obtain the coating after curing; wherein the mass ratio of epoxy resin, xylene, n-butanol, FG@LDH and polyamide is (30-100): (4-20): (2-10): (0.05-0.3): (20-80).

2. The preparation method according to claim 1, characterized in that: In step 1, the substrate to be processed is a metal substrate, and 80-mesh corundum is used, and the sandblasting accuracy reaches Sa2.5 or above. After sandblasting, the metal substrate is washed with clean water and ethanol in turn, dried with cold air, and immersed in an acetone solution.

3. The preparation method according to claim 1, characterized in that: In step 2, calculated by mass percentage, the fluorine content in the fluorinated graphene is 20% to 60%, the average grain size of the fluorinated graphene is 0.5 to 5 μm, and the ultrasonic stirring time is 1 to 2 hours.

4. The preparation method according to claim 1, characterized in that: In step 2, the corrosion inhibitor is one or both of sodium molybdate and disodium sebacate.

5. The preparation method according to claim 1, characterized in that: In step 2, the reaction temperature is 50-100° C. under a nitrogen atmosphere, precipitation is carried out at room temperature for 12-24 hours, and vacuum freeze-drying is carried out for 12-24 hours.

6. The preparation method according to claim 1, characterized in that: In step 3, the ball milling time is 0.5 to 5 hours, and the coating thickness after curing is 30 to 200 μm.

Citation Information

Patent Citations

  • Preparation method of high-adhesion high-corrosion-resistant fluorinated graphene coating

    CN111451107A

  • Modified hydrotalcite / graphene anticorrosive paint

    CN116640494A

  • Multifunctional lubricating anticorrosive material as well as preparation method and application thereof

    CN118460068A

Cited By

  • Anti-corrosion flexible carbon nano polymer coating and preparation method thereof

    CN121227155A